STABILITY INDICATING HPLC METHOD DEVELOPMENT AND VALIDATION FOR SIMULTANEOUS ESTIMATION OF DAPAGLIFLOZIN AND METFORMIN TABLET DOSAGE FORM - NANDRE, DHANSHRI S; AHMED, AEJAZ; GJ, KHAN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objective of this study was to developed and validated for the routine analysis of dapagliflozin (DAPA) and metformin (MET) in API and tablet dosage forms. Methods: The estimation of DAPA and MET was accomplished with C18 column (4.6 × 250 mm and 5 μm particle size) with DAD detector. The mobile phase consists of Methanol: Water 75:25% v/v of pH-3 adjusted with 0.05% OPA at flow rate of 1 mL/min. The detection wavelength was 233nm, respectively. Results: In the developed method, the retention time of DAPA and MET was found to be 5.099 min and 2.165 min. The reverse phase high performance liquid chromatography method produces linear response that were found in the range of 100–500 μg/mL. The limit of detection and limit of quantification for DAPA were found to be 0.06 μg/mL and 0.1855 μg/mL, respectively and for MET 6.09 μg/mL and 18.45 μg/mL, respectively. Calculated information acquired for both the preliminaries roughly coordinates with the information given by design expert programming which shows the genuineness of the chromatographic condition. Conclusion: The developed method was validated according to the ICH guidelines. The linearity, precision, range, and robustness were within the limits as specified by the ICH guidelines. Hence, the method was found to be simple, accurate, precise, economic, and reproducible.